The Effect of STEM-PjBL Learning on Temperature and Heat Material on Student Learning Outcomes at SMPN 2 Bontang - Anggraynie, Rosytha Tri; Qadar, Riskan; Zulkarnaen, Zulkarnaen (Kasuari: Physics Education Journal (KPEJ), 2023)
STEM (Science, Technology, Engineering and Mathematics) is a learning that consists of 4 fields of science, technology, engineering and mathematics. This study aims to determine whether or not there is an influence of the STEM-PjBL learning model on student learning outcomes. This research was conducted at SMP Negeri 2 Bontang, namely 35 students in class VII E. This type of research used quantitative research with the One Group Pretest Posttest method. The research sampling technique used purposive sampling. Collecting data in this study used test techniques which totaled 8 questions in the form of essays. The results showed that the average student learning outcomes before the STEM-PjBL learning model was applied was 28.7 and after the STEM-PjBL learning model was applied the average student score increased to 65.5 with an average N-Gain of 0. 5 which is included in the medium category.